Instagram Sebagai Media Dalam Upaya Peningkatan Umkm Taman Hutan Raya Pakal 1 Melalui Digital Marketing - Fabella Aprilia Duarsa; Niniek Imaningsih; Cholid Fadil (Literasi: Jurnal Pengabdian Masyarakat dan Inovasi, 2022)
This community service activity aims to help MSME actors in increasing their business after the many shocks in the economic area during the Coronavirus pandemic so that they can continue to run and be able to rise from all the losses that have occurred. The most effective effort to do is to do Digital Marketing through various social media stages, one of which is Instagram. The form of promotion in a business is the key to the success of the business. In addition to saving promotion costs, it is also faster in conveying information to the public. This is certainly very beneficial for MSME actors in the Pakal Forest Park area.